Novel Variants Identified in Multiple Sclerosis Patients From Southern China - Wang, Hongxuan; Pardeshi, Lakhansing Arun; Rong, Xiaoming; Li, Enqin; Wong, Koon Ho; Peng, Ying; Xu, Ren-He (Frontiers in Neurology, 2018)
Background: Multiple sclerosis (MS) is an autoimmune and demyelinating disease. Genome-wide association studies have shown that MS is associated with many genetic variants in some human leucocyte antigen genes and other immune-related genes, however, those studies were mostly specific to Caucasian populations. We attempt to address whether the same associations are also true for Asian populations by conducting whole-exome sequencing on MS patients from southern China. Methods: Genomic DNA was extracted from the peripheral blood mononucleocytes of 8 MS patients and 26 healthy controls and followed by exome sequencing. Results: In total, 41,227 variants were found to have moderate to high impact on their protein products. After filtering per allele frequencies according to known database, 17 variants with the allele frequency < 1% or variants with undetermined frequency were identified to be unreported and have significantly different frequencies between the MS patients and healthy controls. After validation via Sanger sequencing, one rare variant located in exon 7 of TRIOBP (Chr22: 37723520G>T, Ala322Ser, rs201693690) was found to be a novel missense variant. Conclusion: MS in southern China may have association with unique genetic variants, our data suggest TRIOBP as a potential novel risk gene.